A hot trick for efficient peptide exchange on MHC class I multimers for large-scale detection of antigen-specific T cells. (October 2022) - Luimstra, Jolien; Garstka, Malgorzata; Neefjes, Jacques; Ovaa, Huib
Abstract : The classical reagents to visualize, characterize and isolate specific CD8+ T cells are MHC I molecules multimerized on a streptavidin backbone. By labelling them with a fluorochrome these multimers can be used for analysis and isolation using flow cytometry. Folding of pMHC complexes is a laborious process that needs to be performed for every peptide separately, a hurdle that many attempted to be overcome by the development of a number of peptide exchange tricks. These methods allow us to fold one large batch of pMHCs and exchange the peptide by applying an appropriate trigger. We have recently published an exchange technology that does not rely on chemicals or UV that can damage the protein, but instead uses temperature to induce exchange. We have designed template peptides for HLA-A*02:01 and H-2Kb with an affinity that is high enough for efficient refolding at 4°C, but low enough for dissociation at elevated temperatures. Whereas preceding technologies required multimerization post exchange, this simple and flexible method can be applied on multimers, thus reducing the number of steps prior to T cell staining. Using this technology multiple MHC I multimers can be generated in parallel, to allow staining and isolation of large sets of CD8+ T cells. We are currently working on designing template peptides for other alleles and optimizing backbones and labelling strategies to further increase the multiplex performance of MHC I multimers.